Penerapan pendidikan karakter dalam budaya sekolah di sekolah dasar - Restu Peni Winahyu; Sri Marmoah; Sularmi Sularmi (Didaktika Dwija Indria, 2020)
Abstract. The purpose of this study to describe the implementation of the character education at SDN Bansari. The study used a qualitative method through a case study approach. The data was taken from ten informants that consisting of the headmaster, third grade classroom teacher, fifth grade classroom teacher, an Islamic education teacher, student of third and fifth grade, the third and fifth graders parent, the chairman of committee, and school employees that selected from purposive technique. Data were taken in depth interviews to all of the informants. The result of the research showed that there are four priority in SDN Bansari. The four values of the character are that: 1) religious; 2) patriotism; 3) communicative; 4) appreciating accomplishment; and 5) environmental concerns. A number of strategies in character education’s implementation were among others, routine activities, role modelling/exemplary, spontaneous activities, conditioning, and programmable. Character education in school culture in SDN Bansari was done by combination of the strategy and character value.